2020
DOI: 10.1016/j.jvs.2019.06.105
|View full text |Cite
|
Sign up to set email alerts
|

Systematic review and meta-analysis of sex differences in outcomes after endovascular aneurysm repair for infrarenal abdominal aortic aneurysm

Abstract: Objective: Women face distinctive challenges when they receive endovascular aneurysm repair (EVAR) treatment, and according to the previous studies, sex differences in outcomes after EVAR for infrarenal abdominal aortic aneurysm (AAA) remains controversial. This study aimed to compare the short-term and long-term outcomes between women and men after EVAR for infrarenal AAA. Methods: We conducted a comprehensive systematic review and meta-analysis of all available studies reporting sex differences after EVAR fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(23 citation statements)
references
References 73 publications
1
17
0
1
Order By: Relevance
“…Furthermore, it has been well-documented that the outcomes of AAA are worse in female patients than in male patients. 6 Previous studies have demonstrated that female sex is independently associated with a faster rate of AAA growth 23 and tends to rupture at a smaller aortic size. 24 Furthermore, some animal studies have demonstrated that estrogen may play a protective role in the development of AAAs, while testosterone has an adverse effect on wall stress.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, it has been well-documented that the outcomes of AAA are worse in female patients than in male patients. 6 Previous studies have demonstrated that female sex is independently associated with a faster rate of AAA growth 23 and tends to rupture at a smaller aortic size. 24 Furthermore, some animal studies have demonstrated that estrogen may play a protective role in the development of AAAs, while testosterone has an adverse effect on wall stress.…”
Section: Discussionmentioning
confidence: 99%
“…Aortic dissection (AD) affects 1.5-to 6-folds more men than women. [1][2][3] Although the sex differences in presentation and outcomes were well known in coronary artery disease 4,5 and abdominal aortic aneurysms (AAA), 6,7 only a few studies have focused on them in the context of AD.…”
Section: Introductionmentioning
confidence: 99%
“…A recent meta-analysis has confirmed significantly higher 30 day mortality in women following EVAR. 13 The outcomes for intact AAA repair in patients over eighty reported in this study were significantly worse overall and particularly for mortality after OSR at 9.3%. Although peri-operative mortality for EVAR was lower at 1.4%, nearly half of all EVAR deaths in this study occurred in this group.…”
Section: Discussionmentioning
confidence: 64%
“…Juxtarenale AAA waren wie in der vorliegenden Untersuchung als solche definiert, wenn die Aortenklemme wenigstens oberhalb der ersten Nierenarterie platziert wurde. Das Krankenhausfallvolumen an juxtarenalen AAA wurde in niedrig (0-<4), mittel (4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14) und hoch (>14 Fälle/Jahr) eingeteilt. In dieser Erhebung war ein geringes Fallvolumen an juxtarenalen AAA mit einer höheren Kliniksterblichkeit assoziiert, mit einer Klinikletalität von 9,0 %, 4,9 % und 3,9 %.…”
Section: Diskussionunclassified